Analisis Upaya Guru Terhadap Kemampuan Membaca Disleksia Kelas V SDN Jatinegara Kaum 14 - Aisyah Hoirunnisah; Dedi Mulia; Sigit Setiawan; Sundawati Tisnasari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Dyslexic reading skills in children with learning difficulties are based on obstacles in reading and spelling. This research focuses on how the teacher's efforts in teaching dyslexic reading skills in children with learning difficulties This research method uses descriptive qualitative methods. Data collection techniques triangulation techniques using interviews, observation and documentation. The subjects of this research using purposive sampling technique are fifth grade teacher, special assistant teacher, principal, and parents. The results showed that the reading ability of grade V dyslexia included an increase in reading ability which initially only syllables now increased to words. The Special Assistance Teacher's efforts towards dyslexic reading skills in children with learning difficulties are carried out by giving attention and motivation to dyslexic children, fostering a sense of enthusiasm in learning, and providing rewards and additional grades to students who have improved in reading.